Tracking and the Intergenerational Transmission of Education: Evidence from a Natural Experiment - Simon Lange; Marten von Werder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Proponents of tracking argue that the creation of more homogeneous classes increases efficiency while opponents fear that tracking aggravates initial differences between students. We estimate the effects on the intergenerational transmission of education of a reform that delayed tracking by two years in one of Germany's federal states. While the reform had no effect on educational outcomes on average, it increased educational attainment among individuals with uneducated parents and decreased attainment among individuals with educated parents. The reform thus lowered the gradient between parental education and own education. The effect is driven entirely by changes in the gradient for males.
Keywords: I21; I24; I28; 330